2006
DOI: 10.1093/europace/eul091
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of mode survival, reliability of atrial sensing and incidence of atrial tachyarrhythmias in 307 single-lead VDD pacemaker patients

Abstract: These data illustrate that single-lead VDD pacemakers can be applied without serious complications in a highly selected group of patients. Our main concern is the development of AT in a large part of our population. Over a 10-year period, two thirds of our patients presented with AT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Previous studies have demonstrated a gradual decrease in the P wave amplitude during the follow-up period. 15,16 Our study also demonstrated that atrial signal measurements decreased by 60% in the period between implantation and last visit. Many factors may affect the quality and the characteristic of the P wave signals.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have demonstrated a gradual decrease in the P wave amplitude during the follow-up period. 15,16 Our study also demonstrated that atrial signal measurements decreased by 60% in the period between implantation and last visit. Many factors may affect the quality and the characteristic of the P wave signals.…”
Section: Discussionsupporting
confidence: 67%
“…The concept VDD pacemaker was designed in 1973, but only became commercially available in the 80s [ 9 ] . Mond et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they may reduce procedure time and some complications associated with dual-chamber implants. They are used infrequently because the atrial sensing ability of the lead has tended to degrade over time, and implanters are concerned about the potential need for atrial pacing if SND develops (95)(96). However, a VDD pacing system can have a potential role in the management of the younger patient, such as the patient with congenital heart block who might expect multiple system revisions over decades of follow-up (see Recommendations Table 1).…”
Section: Single-lead Dual-chamber Vdd Pacemakersmentioning
confidence: 99%